A Communicative Language Teaching Approach in Technology Enhanced English Classrooms: A Linguistic Perspective - Hutauruk, Desi Ramadali; Daulay, Sholihatul Hamidah; Dalimunte, Muhammad (SCOPE: Journal of English Language Teaching, 2024)
This research aims to gain insights into teachers' perceptions and practices regarding CLT principles and their alignment with linguistic theories of language learning. A qualitative approach was used by involving 10 English teachers from different secondary schools in North Sumatra using purposive sampling. Data were collected through semi-structured interviews, classroom observations, and document analysis and analyzed through inductively using thematic analysis. The findings reveal a strong emphasis on authentic language use, development of communicative competence, student-centered and interactive approaches, and integration of digital technology to facilitate real-time communication and collaborative language learning experiences. Therefore CLT and linguistic perspective in the language classroom and potential role of technology in enhancing effective communicative language teaching.